Optimization Optimizing Agrotechnology-Based Crop-Livestock Integration for Productivity and Economic Resilience of Farmers in Seram Bagian Barat Regency - Marlita. H. Makaruku; Esther Kembauw; Vilma Laurien Tanasale; Christian Willem Patty; Nureny Goo (International Journal of Multidisciplinary Sciences and Arts, 2025)
Crop-livestock integration system is an integrated approach in agriculture that has the potential to increase farmers' productivity and economic resilience, especially in rural areas such as West Seram District, Maluku Province. The system relies on a reciprocal relationship between crop and livestock components, where waste from one sector can be utilized as inputs for the other. However, the success of this system is often constrained by pest and disease attacks on crops and livestock, which can reduce production yields and farmers' income. The application of modern agrotechnology is expected to reduce these risks and optimize production potential in a sustainable manner. This study aims to analyze the effectiveness of agrotechnology-based crop-livestock integration systems and their impact on agricultural productivity and farmers' income in villages such as Piru, Lokki, and Waisala. The research method used qualitative and quantitative approaches, with data collection techniques in the form of observation, in-depth interviews, documentation, and questionnaires to 60 farmers who actively implement the integration system. Data analysis was conducted using descriptive and inferential statistical approaches, specifically multiple linear regression analysis. The results showed that the application of agrotechnology-based integration systems had a significant positive impact, including increasing the efficiency of land use and production inputs, reducing farmers' operational costs, and strengthening resistance to biotic disturbances such as pests and diseases. The productivity of crops such as rice and corn increased by an average of 20-25%, while the efficient use of livestock waste as fertilizer and feed increased farmers' household income by 30%. This article recommends improved technology training for farmers, strengthened farmer institutions, and supporting policies from the local government to encourage the replication of sustainable integration systems in the West Seram region.